[Travertine at Lýsuhóll] - Streng, Evelyn Fiedler (1975)
Photograph of travertine rock at Lýsuhóll on Snæfellsnæs Peninsula. The orange rock sits atop black rock along a small stream at the center of the photograph. The rock forms a flat platform, a dark power line visible in the top right corner of the photograph. Grey and white rocks lines the side of the stream to the left. A group of people in blue stands on the rocks at the center of the photograph, looking down at the travertine.